AN ANALYSIS OF EDUCATIONAL VALUE AND DEFENCE MECHANISM IN “LIFE OF PI” NOVEL BY YANN MARTEL - Nurul Azmi Aprianti (Universitas Indraprasta PGRI, 2022)
This research was aimed to analyze an educational value and defence mechanism in life of pi novel by Yann Martel. Life of Pi is an award-winning novel written by Yann Martel, a Canadian author. The novel depicts the topic of struggle for life and against death in an emergency situation. It tells about the struggle of an Indian boy who spent 227 days with a fierce tiger in the Pacific Ocean, and as the sole survivor in a shipwreck that killed his family. There are two problems are formulated to guide and limit the discussion in this study. The first problem examines the description of the educational value, the second problem examines the defence mechanism in that novel. The methodology of this research is descriptive qualitative method. All of the data are gathered by reading the novel, identifying, classifying, and reducing the data. The primary data of the study are in the form of monologues and dialogues of the novel itself. The primary data is supported by secondary data that is taken from books, journals, articles, essays, and sites that relate to the study. The selected data is interpreted into understandable meaning by descriptive technique. The result of the research finds that educational value in life of pi novel: he is intelligent, he was able to enter the best secondary school in his town and later achieved top grades as a university student; open- minded, He is open-minded in his way of thinking; spiritual, He practices three religions with the reason that he wants to love God; and has strong determination, He has a strong will and he does not give up or become desperate easily. The defence mechanism carried out by Pi Patel: by recognizing and using his strength, which is made possible by his intelligence; by being realistic about the situation, which is facilitated by his open- mindedness; and by adopting positive attitude, which is facilitated by his spirituality and strong determination.